2019
DOI: 10.1007/s10948-019-05382-4
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast Carrier Dynamics in an Organic Superconductor κ-(BEDT-TTF)2Cu[N(CN)2]Br by Spectrally Resolved Pump-Probe Spectroscopy

Abstract: In this work, spectrally-resolved optical pump probe measurements were carried out on strongly correlated organic superconductor κ-(BEDT-TTF) 2 Cu[N(CN) 2 ]Br. We find two different types of carrier relaxation dynamics, one of which appears at 1.82 eV and 1.94 eV, and another at 2.17 eV. The former is characterized by short decay time ∼ 1 -2 ps and appears below ∼ 60 K. From the comparison with the previous studies, the dynamics arises from the photoinduced pseudogap (PG) formation of the partially-appeared Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Organic superconductors form another class of superconductors showing the realization of a superconducting dome of multigap superconductivity in superlattices of quantum wires described by Mazziotti [86]. At Superstripes 2019 Tsuchiya et al [87] and Nakagawa et al, [88] have reported the most recent results on the investigation of carrier dynamics and phase separation by spectrally resolved pump-probe spectroscopy and polarized time-resolved spectroscopy of electronic phase separation. Arrested nanoscale phase separation was predicted for multiband correlated metals near a topological Lifshitz transition [89] which is reached by tuning strain and charge [90] with a complex landscape of polaronic short range charge density waves [91].…”
Section: The Superstripes 2019 Conferencementioning
confidence: 99%
“…Organic superconductors form another class of superconductors showing the realization of a superconducting dome of multigap superconductivity in superlattices of quantum wires described by Mazziotti [86]. At Superstripes 2019 Tsuchiya et al [87] and Nakagawa et al, [88] have reported the most recent results on the investigation of carrier dynamics and phase separation by spectrally resolved pump-probe spectroscopy and polarized time-resolved spectroscopy of electronic phase separation. Arrested nanoscale phase separation was predicted for multiband correlated metals near a topological Lifshitz transition [89] which is reached by tuning strain and charge [90] with a complex landscape of polaronic short range charge density waves [91].…”
Section: The Superstripes 2019 Conferencementioning
confidence: 99%
“…An optical pump broadband-probe spectroscopy is a powerful technique to reveal a wide range of photo-induced changes in the electronic spectrum. So far, this technique has uncovered the high-energy spectral change due to the SC transition and pseudogap (PG) formation in cuprates [17,18] and κ-Br [19], as well as carrier relaxation associated with the spin-density-wave state in pnictides [20]. Therefore, by applying this technique to κ-NCS, we can obtain critical insights into the origin of the AP dynamics.…”
mentioning
confidence: 99%